Порівняння показників інформативності ПЛР-маркерів для аналізу генетичного різноманіття на прикладі Gentiana lutea L. - Андрєєв, І.О.; Мосула, М.З.; Мельник, В.М.; Бублик, О.М.; Конвалюк, І.І.; Дробик, Н.М. (Фактори експериментальної еволюції організмів, 2014)
The aim of the work was to compare informativeness indices of PCR-based markers for genetic diversity assessment and select the most efficient from them. Methods. The study involved 30 plants from two G. lutea populations (Svydivets ridge, Ukrainian Carpathians) which were subjected to RAPD, ISSR, CDDP, RGAP, and IRAP analyses. To evaluate the efficiency of the primers, the total number of generated bands, the proportion of polymorphic bands, the resolving power (Rp), the discrimination power (D), the discriminating power (DL), the polymorphism information content (PIC), the marker index (MI) and the number of non-differentiated pairs (ND) were calculated. Results. The informativeness indices were calculated for each primer based on the frequency of individual bands and banding patterns. This was followed by correlation analysis of the indices. A very strong relationship was found between DL and ND, and between MI and proportion of polymorphic amplicons (p < 0.001). There were also high or moderate significant correlations between other parameters, with the exception of PIC. The estimated number of non-differentiated pairs and that determined experimentally were very close for all primers. Conclusions. All of the informativeness indices, except PIC, describe the efficiency of PCR-based markers in some way. The comparison of different markers showed that the most informative was the discriminating power. It can be used successfully to select the primers for genetic diversity assessment, while the confusion probability (C) can be used to determine the minimal set of primers necessary to discriminate between the genotypes in a sample of N accessions.